Type 2 Gaucher disease: the collodion baby phenotype revisited. Issue 2 (1st March 2000) - Stone, D L; Carey, W F; Christodoulou, J; Sillence, D; Nelson, P; Callahan, M; Tayebi, N; Sidransky, E
Abstract : The association of Gaucher disease, the inherited deficiency of lysosomal glucocerebrosidase (EC 3.2.1.45 ), and congenital ichthyosis was first noted a decade ago. Subsequently, a null allele type 2 Gaucher mouse was generated that also exhibited ichthyotic skin, confirming that the skin disorder and enzyme deficiency were directly related. This paper details the clinical and molecular characterisation of 6 cases of type 2 Gaucher disease presenting with the collodion baby phenotype. The identified mutant glucocerebrosidase alleles include two novel mutations (S196P and R131L) and two rare point mutations (R120W and R257Q), as well as alleles resulting from recombination with the nearby glucocerebrosidase pseudogene. There is significant genotypic heterogeneity in this rare subset of patients with type 2 Gaucher disease. Gaucher disease should be considered in the differential diagnosis of congenital ichthyosis in the newborn period.